Devonian subduction and syncollisional exhumation of continental crust in Lofoten, Norway - Froitzheim, Nikolaus; Miladinova, Irena; Janak, Marian; Kullerud, Kare; Ravna, Erling Krogh; Majka, Jaroslaw; Fonseca, Raul O. C.; Muenker, Carsten; Nagel, Thorsten J. (GEOLOGICAL SOC AMER, INC, 2016)
When continents collide, continental crust of the lower plate may be subducted to mantle depth and return to the surface to form eclogite facies metamorphic terranes, as typified by the Western Gneiss Complex of the Scandinavian Caledonides. Proterozoic basement of the Lofoten Islands, located northeast and along strike of the Western Gneiss Complex, contains Caledonian eclogite, although Caledonian deformation is only minor. Previous dating suggested that Lofoten eclogites formed at ca. 480 Ma, i.e., similar to 50 Ma before the collision between the major continents Baltica and Laurentia, and that the Lofoten basement may not originate from Baltica but rather represents a stranded microcontinent. Newly discovered kyanite eclogites from the Lofoten Islands record deep subduction of continental crust during the main (Scandian) stage of Baltica-Laurentia collision ca. 400 Ma. Thermobarometry and thermodynamic modeling yield metamorphic conditions of 2.5-2.8 GPa and similar to 650 degrees C. Lu-Hf geochronology yields 399 +/- 10 Ma, corresponding to the time of garnet growth during subduction. Our results demonstrate that the Lofoten basement belonged to Baltica, was subducted to similar to 90 km depth during the collision with Laurentia, and was exhumed at an intermediate to high rate (>6 mm/yr) while thrusting of a Caledonian allochthon (Leknes Group) was still ongoing. This supports the challenging conclusions that (1) subducted continental crust may stay rigid down to a depth of similar to 90 km, and (2) it may be exhumed during ongoing collision and crustal shortening.